The Effects of Injury Experiences on the Quality of Life in South Korean Adults Aged 20 Years or Over - Lee, Yoon-Ho; Park, Hae-Ryoung; Park, Sang-Sub (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to determine the effects of injury experiences on the quality of life. Injury can have a diversity of health-related effects, including activity restrictions, walking, and stress. This study used coded raw data.Methods/Statistical analysis: The raw data from “The Seventh Korea National Health and Nutrition Examination Survey(KNHANES Ⅶ-2)” were used. The surveys were the health survey, the physical examination survey, and the nutrition survey. Of these, the health survey was used as an instrument. EQ-5D in the health survey was used for the quality of life. Of 8,127 respondents, a total of 6,113 were included, with the exception of 2,014 aged